Peran Sektor Pertanian Dalam Perekonomian Provinsi Banten - Aris Muchendar; Aliudin Aliudin; Dian Anggraeni (JURNAL AGRIBISNIS TERPADU, 2020)
Development of agriculture until nowdays played important role in Banten province eonomy. this research aims to analyze the role of economic sector in  Banten province and analyze the linkages of economic sectors to other  economy sector in banten province. the analytical method used in this reseach quantitative analysis using input-output analysis. the analysis showed that  livestock subsector has a higher value backward lingkages  is 1.5319. Meanwhile plantfood sector has a higher value forward lingkage  in agriculture sector is 1,6734.  livestock subsector are the only one subsector in agriculture  who has distribution index value and sensitivity of dispersion (>1) and in first quadran.